The Intellectual and Spiritual Contribution of Nuruddin Ar-Raniri to Islamic Education in Indonesia - Mwamburi Adam Hamisi; AbdulGafar Olawale Fahm (Jurnal Pendidikan Islam, 2017)
This paper attempts to analyze the intellectual and spiritual contributions of Nuruddin ar-Raniri to Islamic education in Indonesia. It gives the genealogy of ar-Raniri and his arrival to Indonesia as well as the vital role he played in the documentation of important literatures in Malay and Islamic education. This paper further argues that Nuruddin ar-Raniri, serving as a Sufi scholar, great writer, theologian, historian has immense contribution. His impact and influence in Indonesia was profound and noteworthy. His contribution to Malay literature and Islamic education is unavoidable. His masterpieces on intellectual writings has exerted considerable effort in the field of Malay letters and historical writings. His writings cover various fields of knowledge which helped in developing the learning culture in the society. This study used a qualitative approach in collecting and analyzing the data. This study concludes that due to this great contribution in the field of Islamic knowledge, ar-Raniri emerged as an exceptional scholar of his time and a pioneer in the standardization of Islamic religious text within Indonesia. Thus, it remains a legacy and a significant contribution in transforming Indonesia spiritually and intellectually. His contribution in Islamic education includes learning material and Islamic traditional book delivered in Pegon language which used in pesantren and other Islamic education institutions in Indonesia.